Children Malnutrition in Mazahua Communities with Transnational Male Migration - Diego Acosta, Liliana (2009)
The objective was to evaluate the prevalence of malnutrition in children aged 1-5 years according to gender in transnational male migration and non-migration households in two communities of the Mazahua region in the State of Mexico. The sample studied was 534 children from one to five years old (50.4% boys and 49.6% girls). The nutritional condition was evaluated based on weight/age, weight/height and height/age, indicators recommended by the Mexican Official Norm NOM-031-SSA2-1999 (Secretaría de Salud, 1999) and the World Health Organisation (WHO). Differences in nutrition were established by standard deviation analysis. The prevalence of malnutrition according to height was 57.1%, for weight and age it was 43.1%, and for weight and height it was 10.1%. There is no significant difference between the indicators related to transnational male migration.